2012
DOI: 10.1007/s13213-012-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the biochemical traits of novel Trichoderma-based biofilms for use as plant growth-promoting inoculants

Abstract: Bacteria-mediated plant growth promotion is a well-established and complex phenomenon that is often achieved by the activities of more than one plant growthpromoting (PGP) trait, which may not always be present in a single organism. Biofilms developed using a combination of two organisms with useful plant growth-promoting rhizobacteria (PGPR) traits may provide a definite advantage. In this context, in vitro studies were conducted evaluating the PGP traits of novel biofilms developed using Trichoderma as matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…Biofilms also showed increase in HCN and ammonia production as compared to their individual partners, which are correlated to antifungal activity. Similar results were observed by Triveni et al [7] in case of B. subtilis-T. viride and P. fluorescens-T. viride biofilms. Arfaoui et al [17] has reported suppression of Fusarium wilt of chickpea under in vitro and in vivo conditions by six rhizobial strains positive for HCN production.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Biofilms also showed increase in HCN and ammonia production as compared to their individual partners, which are correlated to antifungal activity. Similar results were observed by Triveni et al [7] in case of B. subtilis-T. viride and P. fluorescens-T. viride biofilms. Arfaoui et al [17] has reported suppression of Fusarium wilt of chickpea under in vitro and in vivo conditions by six rhizobial strains positive for HCN production.…”
Section: Discussionsupporting
confidence: 90%
“…In the last few years the focus has shifted from single inoculation to coinoculation to use of consortium of microorganisms to obtain maximum benefits. Another strategy developed is the biofilmed biofertilizers wherein fungi, cyanobacteria or bacteria are used as matrix and agriculturally important bacteria like Azotobacter, Rhizobium, Bacillus and Pseudomonas are used as associate partners [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Triveni et al, (2013) highlighted that compost and vermiculite (1:1) was a suitable carrier for the novel biofilmed biofertilizers. Triveni et al, (2012) recorded Trichoderma -Azatobacte r biofilm was recorded the highest nitrogenase activity and ACC deaminase activity. Xuan et al, (2012) reported maximum concentration of soluble phosphorus (P) was determined in the mixed culture of P. chlororaphis and A. pascens.…”
Section: In Vitro Development Of Biofilmsmentioning
confidence: 89%
“…micas and feldspars) (Sparks and Huang, 1985) or the addition of K fertilizers. Many microorganisms in the soil are able to solubilize 'unavailable' forms of K-bearing minerals, such as micas, illite and orthoclases, by excreting organic acids which either directly dissolves rock K or chelate silicon ions to bring the K into solution (Groudev, 1987;Friedrich et al, 1991;Ullman et al, 1996;Bennett et al, 1998). Biofilm formation of this zinc solubilizers and potassium releasers has an immense importance in agriculture.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2037-2047mentioning
confidence: 99%
See 1 more Smart Citation